From the laboratory to the field, from senses to social change: Development and perspectives of Croatian psychology - Čorkalo Biruški, Dinka (2004)
In 1999. Department of Psychology at the University of Zagreb celebrated the 70th anniversary of its existence and a relatively long history of formal education of psychologists in Croatia. It was an opportunity for psychological profession to look back, to see where it stands in the light of its own history but also in the light of the development of the European psychology. It was also an opportunity for Croatian psychology to view perspectives of future development of the discipline. During its history, psychology in Croatia went trough important changes in several aspects. Regarding education these changes could be followed from relatively modest beginnings in 1929 when Ramiro Bujas established psychology as an independent university program. The founders of so called Zagreb psychological school insisted from the very beginning on scientific ground of the discipline, empirical approach and especially on the experiment as the basic method. Experimental tradition and general methodological rigorousness have remained the most important characteristic of the Croatian psychology. In the beginning of its development psychology in Croatia was relatively isolated within laboratory. The most prominent research activity in those days was in the area of “ simple” psychological processes like galvanic skin response and the research of the senses. However, this research had an important echo in a wider professional audience. With the development of the discipline, enlargement of the number of psychologists and with opening of psychological laboratory to the real-life problems, many psychologists turned to more applied issues in the areas of educational and industrial psychology and clinical practice. In the last decade the course of development was strongly marked by social changes and war. While maintaining an empirical discourse and scientific criticism, psychologists started to research intensively social phenomena that have emerged from general social changes. Until then relatively rarely investigated issues like ethnic distance, national identity and nationalism, changes of value system, organizational changes and a like, came to the focus of intensive research activity. With the beginning of the war psychologists involved directly in helping the war victims, formulated their knowledge and experiences in well elaborated programs of psychosocial help. This practical work was accompanied by extensive research on the impacts of war on mental health so we can say, not without proud, that many Croatian psychologists today are recognized in a wider professional community as distinguished experts.
Projekt MZOS
ENG